Design and Implementation CCTV on Cloud - Ibnu Asror (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2016)
Today, CCTV technologies are really needed for security survellince. CCTV is not only used for security, butcan be used as monitoring for learning activity in the class room. The problem appears when we needmassively CCTV device. The more CCTV device needed, the more resources computer. Some resourcesexample: Memory, CPU, Bandiwdth, and Power. One of the solutions that for optimize resource is cloudtechnology. The implementation of CCTV system with cloud can optimize CPU, bandwidth, and Power.While, the memory utilities is not significant.